(untitled) (JOURNAL OF SOFTWARE ENGINEERING TOOLS & TECHNOLOGY TRENDS, 2022)
A purely decentralized application meant to share resources/funds online with the most hassle-free and provide a reliable solution that is not supported by any intermediate, centralized authority and provides transparency with a perfect peer-to-peer approach. This system works to fulfil two of the most important requirements. Internet promised but was not able to solve and are the biggest question on the security of any application, data, network, etc. This decentralized approach is based on blockchain and hence is paired with concepts of digital signature that can protect the integrity of the data that is registering or passing over channels; and Time stamping that helps to maintain the records of the date, day, and time of the transfer of the data happening in the network. This prevents the unfortunate dual transits of a single block to two different nodes and works as a computational proof for the chronological order of transactions. All together, these create a blockchain network that works like an immutable ledger that is computationally impractical to reverse once passed, saving people from frauds and an unauthentic act of corrupting the system. Majorly, this system can state to be safe until the honest nodes together have control over the CPU power over any cooperating group of attackers.